A TEACHING STRATEGIES FOR CHILDREN ATTENTION DEFICIT HYPERACTIVITY DISORDER (ADHD) IN ELEMENTARY SCHOOL - Indah Cahyani Putri; Neni Hermita; M. Jaya Adi Putra (Jurusan Pendidikan Luar Biasa, 2026)
This study aims to describe teachers’ strategies for teaching children with Attention Deficit Hyperactivity Disorder (ADHD) in elementary school and to identify the challenges faced during the learning process. The study employs a qualitative approach with a descriptive qualitative design. Data were collected through observation, interviews, and documentation involving classroom teachers, special education teachers, and students with ADHD in an inclusive elementary school. Data analysis utilized the Miles and Huberman model. The results indicate that children with ADHD experience difficulties in maintaining focus, exhibit impulsive behavior, and display excessive motor activity, all of which impact the learning process. Teachers also face challenges such as limited understanding of ADHD, a lack of learning materials, and insufficient time for individual support. To address these issues, teachers implement various strategies, such as the use of visual and concrete materials, activity-based learning, brief and structured instructions, individualized approaches, and positive reinforcement. This study demonstrates that adaptive learning strategies and an inclusive learning environment can help increase the engagement of children with ADHD in the learning process.